Glaucoma Treatment and Hydrogel: Current Insights and State of the Art - Antonio Maria Fea; Cristina Novarese; Paolo Caselgrandi; Giacomo Boscia (Gels, 2022)
Aqueous gels formulated using hydrophilic polymers (hydrogels) and those based on stimuli-responsive polymers (in situ gelling or gel-forming systems) attract increasing interest in the treatment of several eye diseases. Their chemical structure enables them to incorporate various ophthalmic medications, achieving their optimal therapeutic doses and providing more clinically relevant time courses (weeks or months as opposed to hours and days), which will inevitably reduce dose frequency, thereby improving patient compliance and clinical outcomes. Due to its chronic course, the treatment of glaucoma may benefit from applying gel technologies as drug-delivering systems and as antifibrotic treatment during and after surgery. Therefore, our purpose is to review current applications of ophthalmic gelling systems with particular emphasis on glaucoma.